2010
DOI: 10.1139/o09-183
|View full text |Cite
|
Sign up to set email alerts
|

Structures and ice-binding faces of the alanine-rich type I antifreeze proteinsThis paper is one of a selection of papers published in this special issue entitled “Canadian Society of Biochemistry, Molecular & Cellular Biology 52nd Annual Meeting — Protein Folding: Principles and Diseases” and has undergone the Journal's usual peer review process.

Abstract: Antifreeze proteins (AFPs) protect cold-blooded organisms from the damage caused by freezing through their ability to inhibit ice growth. The type I AFP family, found in several fish species, contains proteins that have a high alanine content (>60% of the sequence) and structures that are almost all α-helical. We examine the structure of the type I AFP isoforms HPLC6 from winter flounder, shorthorn sculpin 3, and the winter flounder hyperactive type I AFP. The HPLC6 isoform structure consists of a single α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…However, the adsorption inhibition mechanism has one major assumption: irreversible binding of antifreeze proteins [76]. The problem with reversible binding is that transient desorption of antifreeze can reveal new sites for energetically favourable additions of water molecules; this can lead to uncontrollable ice growth [74].…”
Section: Biochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the adsorption inhibition mechanism has one major assumption: irreversible binding of antifreeze proteins [76]. The problem with reversible binding is that transient desorption of antifreeze can reveal new sites for energetically favourable additions of water molecules; this can lead to uncontrollable ice growth [74].…”
Section: Biochemistrymentioning
confidence: 99%
“…These repeats are non-specific but are structured so that ice binding residues are aligned on one side to create an ice binding face [26, 28, 29, 76]. Furthermore, regularity of repeats creates order in the spacing between ice binding residues, which is essential to complement ice crystal planes.…”
Section: Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…It has three repeated sequences, which contain 11 amino acid repeats; Thr-Ala-Ala-X-Ala-X-X-Ala-Ala-X-X, where X can be any amino acid. The crystal structure of the HPLC6 AFP (PDB code 1WFA) [36] revealed that this has an amphipathic right-handed α-helical conformation with N - and C -terminal cap structures to ensure its stability in solution. The N - and C -terminal cap structures are stabilized by a hydrogen bond network that involves structurally ordered water molecules, and help the protein maintain its helicity (Figure 1A).…”
Section: Type I Antifreeze Peptidesmentioning
confidence: 99%
“…Type I AFPs are alanine-rich peptides found in blood samples from winter flounder ( Pseudopleuronectes americanus ) and shorthorn sculpin ( Myoxocephalus scorpius ). To date, three-dimensional (3D) structures of the AFPs HPLC6 and ss3 have been solved [36,37] and their ice-binding residues have been identified using structure-based mutagenesis studies. Accumulated structure-function relationship studies on Type I AFPs have revealed that common Ala-rich hydrophobic regions are essential for potent antifreeze activity [36].…”
Section: Introductionmentioning
confidence: 99%